Toward a Common Understanding of Ocean Multi-Use - Schupp, Maximilian Felix; Bocci, Martina; Depellegrin, Daniel; Kafas, Andronikos; Kyriazi, Zacharoula; Lukic, Ivana; Schultz-Zehden, Angela; Krause, Gesche; Onyango, Vincent; Buck, Bela H. (Frontiers in Marine Science, 2019)
The ‘open ocean’ has become a highly contested space as coastal populations and maritime uses soared in abundance and intensity over the last decades. Changing marine utilization patterns represent a considerable challenge to society and governments. Maritime spatial planning has emerged as one tool to manage conflicts between users and achieve societal goals for the use of marine space; however single-sector management approaches are too often still the norm. The last decades have seen the rise of a new ocean use concept: the joint ‘multi-use’ of ocean space. This paper aims to explain and refine the concept of ocean multi-use of space by reviewing the development and state of the art of multi-use in Europe and presenting a clear definition and a comprehensive typology for existing multi-use combinations. It builds on the connectivity of uses and users in spatial, temporal, provisional, and functional dimensions as the underlying key characteristic of multi-use dimensions. Combinations of these dimensions yield four distinct types of multi-use with little overlap between them. The diversity of types demonstrates that there is no one-size-fits-all management approach, but rather that adaptive management plans are needed, focusing on achieving the highest societal benefit while minimising conflicts. This work will help to sharpen, refine and advance the public and academic discourse over marine spatial planning by offering a common framework to planners, researchers and users alike, when discussing multi-use and its management implications.